Formation of Integration and Pedagogical Skills of the Future Teacher of Music Art in the Conditions Master’s Degree - Bezemchuk, Larisa; Fomin, Volodymyr (Professional Art Education, 2021)
The purpose of the article is to study the formation of integration and pedagogical skills of future music teachers and to determine effective forms of professional training of students during master ‘s studies.Methods & methodology. Conventional pedagogical research methods were applied: theoretical analysis of scientific and pedagogical literature, comparative analysis, empirical and modeling methods. In the course of the study, the essence of integration and pedagogical skills was theoretically substantiated in the context of solving the issues of professional training of the future teacher of musical art on the principle of interdisciplinary integration.Scientific novelty. The stage of formation of integration-pedagogical skills is highlighted: late-developmental, reproductive-creative, independent-creative and structural-thematic content scheme of integration connections of inter-disciplinary express course for masters "Integration of art into school", which plays the role of a mini-orenter for applicants who come to the magistracy of the specified specialization but have different levels of musical training and directions of qualification preferences. A schematic version of the content of the topics of qualification disciplines "Music Pedagogy" is presented.Results. It is determined that the design of educational programs for students in the specialty 014 Secondary education (Musical art) orients applicants of both the first bachelor's level and the second master's level to the formation of a special integration and pedagogical skills. It has been proved that this type of skills is a priority for mastering the interdisciplinary express course, the integration and pedagogical core for which there is a didactic creative module of art lessons of integrated content. It is proposed to carry out the course structuring on the basis of integration links between the disciplines of the general training cycle and the training courses "Methodology of teaching qualification disciplines" and "Workshop on qualifications". The interdisciplinary express course highlights the range of issues related to the specialty "Teacher of musical art", "Teacher of integrated art course".Conclusions. Summing up the results of the study, it can be noted that practical training on the formation of integration and pedagogical skills of the future teacher of musical art should be carried out in the plane of three content lines "The essence of integration in art education", "Conceptual bases of the method of the integrated course "Art", and "Artistic and pedagogical technologies in music education".
Keywords: teacher; teachermusic art; artintegration; pedagogical skills; master's degree; nterdisciplinary; express courseВидалити express course